Donor vigilance data of a blood transfusion service: A multicenter analysis. Issue 2 (October 2015) - Burkhardt, T.; Dimanski, B.; Karl, R.; Sievert, U.; Karl, A.; Hübler, C.; Tonn, T.; Sopvinik, I.; Ertl, H.; Moog, R.
Abstract: Background: Donor vigilance is an important part of the quality management system of blood transfusion services. The evaluation of donor side effects helps to improve the donation process and donor compliance. The aim of the present study was to evaluate donor vigilance data in whole blood and plasmapheresis donors of a blood donor service. Materials and methods: Donors fulfilling current national and European eligibility criteria underwent whole blood and plasmapheresis donation (PCS and MCS+ (Haemonetics, Braintree, USA), A 200 (Fenwal, Round Lake, USA). Whole blood was collected at fixed and mobile sites while plasmaphereses were performed at 8 plasma centers. From 2011 to 2013 donor information was provided for gender, age, body weight, height, first and repeat donation. Donors were monitored for venipuncture and circulatory associated side effects. Results: The total incidences of adverse events were 5004 (0.56%) in repeat donors and 2111 (2.78%) in first time donors for whole blood donation and 3323 (1.01%) and 514 (7.96%) for plasmaphereses, respectively. Circulatory associated events were 2679 (0.30%) for whole blood donation and 1624 (0.49%) for plasmaphereses. Conclusion: Our donor vigilance data of a blood transfusion service show that whole blood and plasmapheresis are safe with low incidences of adverse events. Repeat donation and age are predictors for low rates of adverse events. On the other hand, first time donation and female gender were associated with higher incidences of adverse events.